2018
DOI: 10.1016/j.vetpar.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and molecular characterization of systemic isosporosis (atoxoplasmosis) in captive green-winged saltator (Saltator similis)

Abstract: Systemic isosporosis, also called atoxoplasmosis or visceral coccidiosis, is a disease that affects birds in general. Pathogenesis of systemic isosporosis and its etiologic agent have not been well characterized, but taxonomically Atoxoplasma is currently considered a junior objective synonym of Isospora. The present report aimed to describe pathological and molecular findings of systemic isosporosis in captive green-winged saltators (Saltator similis) from the State of Espírito Santo, Brazil. In a commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…While infections can be incidental, higher population densities and mixed-species aviaries make clinical isosporiasis a concern due to the potential for stress and high environmental parasite burdens. Additionally, reports of severe isosporiasis in birds from conservation breeding programs have resulted in a heightened awareness of birds' exposure to non-host-adapted parasites (11)(12)(13). This is of particular concern for rare and endangered species, as well as those bred for release into the wild that may expose threatened free-ranging populations to a novel pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…While infections can be incidental, higher population densities and mixed-species aviaries make clinical isosporiasis a concern due to the potential for stress and high environmental parasite burdens. Additionally, reports of severe isosporiasis in birds from conservation breeding programs have resulted in a heightened awareness of birds' exposure to non-host-adapted parasites (11)(12)(13). This is of particular concern for rare and endangered species, as well as those bred for release into the wild that may expose threatened free-ranging populations to a novel pathogen.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 5 , 6 , 10 One report also found intraendothelial merozoites in green-winged saltators ( Saltator similis ). 8 In our study, we observed that white-rumped shamas appear to have a unique, macrophage-dominant response associated with isosporosis. Lymphocytes were present in most but not all cases.…”
mentioning
confidence: 48%
“…infection in free-ranging birds may not result in a significant mortality rate. Affected birds show prominent keel bones and severe pectoral muscle atrophy associated with thickening of the small intestine ( 75 ) due to lymphocytic proliferation ( Figure 3 ). At least two confirmed outbreaks of the infection primarily affected two flocks of Paroaria coronata , although it spread to some Saltator spp.…”
Section: Discussionmentioning
confidence: 99%